THE INFLUENCE OF JOB FLEXIBILITY ON ONLINE DRIVER PERFORMANCE MEDIATED BY JOB SATISFACTION - Huda, Fatkhul; Ekhsan, Muhamad (Universitas Muhammadiyah Tangerang, 2023)
In the current technological era, humans need travel services that are easy to get to help with daily activities, such as online transportation. Service companies are now competing with each other to create online- based transportation applications. One of the popular online transportation applications in Indonesia is Gojek. The purpose of this study is to determine the effect of work flexibility on online driver performance mediated by job satisfaction at PT. Gojek Indonesia The population used in this study were Gojek drivers in the JABODETABEK area. The type of research used in this study was quantitative research. The data source used is primary data both from the results of questionnaires and survey data or journals. The sampling technique used the Hair et al 2010 formula, and the sampling in this study was carried out by distributing questionnaires with a total sample of 77 respondents. The analysis technique used in this study is multiple linear regression analysis using SMART PLS version 3.0. Based on the findings of this study, it will help companies improve the performance of drivers that there is a study of work flexibility when it is more seriously carried out, this is the fruit of an effort to apply drivers to be able to manage their work time so that they can manage their own work so that work time is not disturbed others and feel satisfied with their work and it will all make their performance increase